Pelaksanaan Pembinaan Kemandirian Narapidana Di Lembaga Pemasyarakatan Kelas II A Bengkalis Kabupaten Bengkalis - Juliana, Septa (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2015)
The background of this research is still common phenomena such as the absence of any significant change of attitude and behavior of the former inmates after returning the society and there are many former inmates who have been free re-do a variety of crimes, so not yet seen the impact of coaching implemented by Corrections for serving his sentence. The population in this study are all the people who live in the area Bengkalis, whereas the sampled are parties involved in the coaching program prisoners held by the Penitentiary Class II A Bengkalis, the Head of the Penitentiary Class II A Bengkalis sand, Head of Section, Head of Section, Head of Officer prisons, prisoners and inmates Team coach. In this study the authors used a combination of qualitative methods and quantitative means to conduct an analysis of the implementation of the coaching prisoners held by the Penitentiary Class II A Sand Bengkalis are then elaborated based on information obtained through questionnaires distributed to the respondents and in-depth interviews and the data are already in the form of documents. Based on a study of 44 respondents by means of questionnaires and conduct in-depth interviews can be concluded that the implementation of coaching prisoners held by the Penitentiary Class II A Bengkalis is still not good, as seen from the indicators of personality development and fostering independence. The obstacles faced by the Penitentiary Class II A Sand Bengkalis in implementing guidance to inmates is insufficient operating budget available, the lack of technical personnel in the field of coaching inmates, yet complete supporting facilities and infrastructure development as well as the lack of cooperation inmates in coaching programs and inmates are not seriously follow the coaching program implemented.